2016
DOI: 10.1371/journal.pone.0165002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Varied Label Designs for Use with Medical Devices: Optimized Labels Outperform Existing Labels in the Correct Selection of Devices and Time to Select

Abstract: PurposeEffective standardization of medical device labels requires objective study of varied designs. Insufficient empirical evidence exists regarding how practitioners utilize and view labeling.ObjectiveMeasure the effect of graphic elements (boxing information, grouping information, symbol use and color-coding) to optimize a label for comparison with those typical of commercial medical devices.DesignParticipants viewed 54 trials on a computer screen. Trials were comprised of two labels that were identical wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The limited work that has been done to understand how packaging performs in healthcare contexts has focused on perioperative environments [ 27 , 34 , 35 ]. Many of the published findings conducted in these more controlled contexts of care indicate improvements in packaging are needed, parallel to the findings we present here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited work that has been done to understand how packaging performs in healthcare contexts has focused on perioperative environments [ 27 , 34 , 35 ]. Many of the published findings conducted in these more controlled contexts of care indicate improvements in packaging are needed, parallel to the findings we present here.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the published findings conducted in these more controlled contexts of care indicate improvements in packaging are needed, parallel to the findings we present here. Published studies using perioperative contexts have concluded that packages are: “hard to open” [ 35 , 36 ] and employ “crowded label contents” which make crucial information difficult to locate [ 27 , 34 , 35 ]. While our survey of paramedics echoed the difficulties voiced by perioperative personnel, they also expressed problems, and coping strategies, that were uniquely their own.…”
Section: Discussionmentioning
confidence: 99%
“…Power estimates were based on our prior work investigating medical device labeling in which participants made a speeded selection between two packages given a criterion (i.e., was latex free). 32 Across trials, critical information (latex, expiration date, sterility, etc.) was highlighted or not.…”
Section: Power Calculationsmentioning
confidence: 99%